Pemutusan Hubungan Kerja yang Tidak Sah dan Pelanggaran Hak-Hak Pekerja: Sebuah Analisis Melalui Yurisprudensi Muamalah Islam dan Undang-Undang Ketenagakerjaan Indonesia - Al'Amin, Dzulkifli; Amriyani, Riza (Universitas Islam Negeri Alauddin Makassar, 2026)
Cases of employment termination that disregard workers' statutory rights remain a recurring problem in Indonesia's industrial relations landscape. This study examines one such case — Court Decision No. 29/Pdt.Sus-PHI/2023/PN Mks — in which a worker was dismissed unilaterally without receiving legally mandated severance and compensation. Using a normative juridical approach with conceptual and statutory analysis, this study draws on court documents and relevant legal literature to investigate how both Islamic muamalah jurisprudence and Indonesian labor law address wrongful termination. The findings show that Indonesian labor law, particularly Law No. 13 of 2003 and its amendment under Government Regulation in Lieu of Law No. 2 of 2022, explicitly requires severance pay and procedural fairness in any termination process. From the perspective of fiqh muamalah, unilateral dismissal without prior deliberation and without fulfillment of the worker's rights contradicts the foundational principles of ijarah — a contractual relationship that demands mutual consent and equitable treatment between employer and employee. The case under study reveals a clear violation of both legal frameworks, compounded by weak enforcement mechanisms. This study argues that stronger integration between Islamic legal values and national labor regulation, alongside consistent judicial and administrative enforcement, is essential to building a more just employment protection system in Indonesia.